Developing Entrepreneurial Orientation Through Catur Purusa Arta (CPA) Culture on Village Credit Institution (VCI) - I Gede Riana; I Wayan Pradnyantha Wirasedana (Journal of Multidisciplinary Academic, 2018)
One of micro finance institution that has proliferated in Bali is Village Credit Institutions (VCI). VCI is a kind of micro finance institution which the owner by the traditional village and the only one micro finance institution that is managed by customary in Indonesia. This study aimed to analysis the effect of entrepreneurial orientation on VCI performance with Catur Purusa Arta (CPA) culture as a moderating variable. The research was conducted at Gianyar, Bali with 86 VCI as a sample. Methods of the data collection used interview techniques and questionnaires. Before analysis, the data qualify was test validity and reliability using SPSS. Furthermore, the data have collected was analysis using descriptive analysis and Moderation Regression Analysis (MRA). The results showed that entrepreneurial orientation is significantly affect on VCI performance. CPA is not significant effect on VCI performance. Moreover, the findings explained that CPA not significant strengthen in the effect of entrepreneurial orientation on VCI performance.